Enhancing self-efficacy to resist body shaming in Jacqueline Wilson's Lola Rose - Toh, Florence Haw Ching; Liau, Agnes Wei Lin (Universiti Putra Malaysia Press, 2020)
Jacqueline Wilson is a former Children’s Laureate whose contemporary realistic children’s novels have been translated into over 30 languages for her predominantly pre-adolescent and teen-girl readers. However, many adults feel that her works are unsuitable for children due to the contemporary realistic issues discussed. This has resulted in a gap within the scholarship devoted to serious analyses of her books. The paper discusses her novel, Lola Rose (2003), with attention given to Lola Rose, the pre-adolescent girl protagonist. It looks at how Lola Rose suffered from her mother’s repeated acts of body shaming, causing her to carry a negative body image and sense of insecurity. Using the concept of self-efficacy expounded by Albert Bandura in his work, Self-efficacy: The exercise of control (1997), the research examines how sources of efficacy information such as enactive mastery experience, vicarious experience, verbal persuasion, and improved physiological and affective states, enhance Lola Rose’s sense of agency. This empowers her to resist the destructive forms of body shaming experienced. The paper argues that contemporary realistic children’s novels such as Wilson’s are useful tools to empower children in overcoming the threats of body shaming.